Synthesis and Characterization of 1-Isonicotinoyl/1-Carboxamido/1-Thiocarboxamido- 3-(2-hydroxy-5-chlorophenyl)-4-aroyl-3-methyl pyrazoles - Jamode, V.S.; Kale, A.S. (Asian Journal of Chemistry, 2010)
Chromone, the starting material for the preparation of 3-methyl pyrazole, is prepared from 2- hydroxy-5-chloro dibenzoyl methane by the action of acetic anhydride and fused sodium acetate in an oil bath at 160ºC for 30 min. 1,4,5-Trisubstituted pyrazoles are obtained by refluxing the mixture of 3-benzoyl-2-methyl-6-chloro-chromone and nucleophiles sch as isonicotinic acid, semicarbazide and thiosemicarbazide in methanol medium. The structures are confirmed by IR and NMR spectral data.